Chapter Bow and Arrowheads from Ancient Macedonia: From Hunters to Archers - Bellas, Ioannis (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
A passage by Demosthenes, who emphatically stated that it was through light infantry troops and their flexibility, rather than the sluggish Macedonian phalanx, that Philip II of Macedon secured his victories, illustrates how important the organization of light infantry units was to Philip ΙΙ. After describing the lightly armed soldiers, the cavalry, and the mercenaries, Demosthenes made reference to archers. Based on this passage and the rich assemblage of arrowheads discovered in ancient Olynthos and Stagira – Greek cities once besieged by Philip II – the author will try to approach the problem of the presence of archers in Philip’s army. First of all, the analysis of the collected data shows that in both areas the presence of specific categories of arrowheads is evidence of the siege laid by Philip’s troops; secondly, it shows that Philip managed to organize a remarkable corps of Macedonian archers in a relatively short period of time. Although their contribution to Philip’s victories was underestimated by the researchers, it seems that in fact, they played a very important role, especially in the difficult conditions of urban combat.